Temporal trend for respiratory diseases in the city of Salvador - doi:10.5020/18061230.2011.p31 - Cardoso, Jefferson Paixão (2012)
Objective: To investigate the distribution and temporal trend of major respiratory diseases in Salvador, Bahia, Brazil, between 1998 and 2007. Methods: Ecological study of aggregate time series that used the database DATASUS as source of information for hospital admission due to respiratory causes. Then, we constructed standardized rates of hospital admissions for pneumonia, asthma and Chronic Obstructive Pulmonary Disease (COPD) by gender and age group for the years studied. Results: The asthma and pneumonia showed a higher morbidity among individuals below 15 years and COPD among individuals over 59 years. The hospitalization rate for asthma decreased from 109.89 per 100,000 in 1998 to 19.67 per 100,000 in 2006. Regarding gender, men had higher rates of hospitalization for the three diseases studied. Other respiratory diseases ranged between 18.0% and 37.3% between the years studied. Conclusions: The results demonstrated trend of reduction on rates of hospital admissions for pneumonia, asthma and COPD in the years 1998 to 2007. Prevention and control measures constituted allies to reduce morbidity of these diseases.